A Critical Analysis of Fraud Cases on the Internet - Syed Anas Ansar, Jaya Yadav, Sujit Kumar Dwivedi, Ankur Pandey, Savarni Prakash Srivastava, Mohammad Ishrat, Mohd Waris Khan, Dhirendra Pandey, Raees Ahmad Khan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We lived in the era of technology, where online websites have made communication and interaction much easier than the early decade. The modern world is changing so quickly, and emerging new trends simplify our lives, but on the other hand, it will also create risks. A website acts as a more admired platform by the user to access the different web applications. Because of the functions of the website, all the data on the website is available in the proper structure, which makes the working environment much convenient and efficient. The websites may undoubtedly be a precious resource for young people, but it may also cause severe problems. It is really easy to build a fake website that looks like an original website where hackers like to deceive consumers and businesses for their own benefits. In this paper, researchers have examined online fraud cases through web applications and how fraudulent websites affect financial loss. Researchers also highlighted the current situation regarding the usage of online services, as well as the threats that have an impact on users. In addition, researchers have suggested that new laws and regulations will be implemented for preventing cybercrime.